Investigating the Environmental and Tourism Importance of Sabzak Dam in Badghis Province - Rahimi, Abdul Ghani; Jalat, Maroof; Ghorzang, Shafiullah (Journal of Natural Sciences – Kabul University, 2026)
This research was conducted in 2024 by distributing questionnaires and conducting face-to-face interviews to investigate the environmental and tourism importance of Sabzak Dam in Badghis province. The results of the research showed that the ecological benefits of Sabzak Dam include combating climate change, preserving biodiversity, providing a fresh water source, generating economic resources, reducing pollution, and supporting ecotourism. Most of the respondents stated that the threatening factors of Sabzak Dam are climate change and cutting down of arche trees. The Sabzak Dam can help the local people's economy by creating jobs, increasing incomes, and attracting tourists. The respondents also stated that people's tourism revenue is spent on restaurant meals, oil, passenger transport, and food. In conclusion, by hosting local festivals, creating facilities for tourists, and advertising on social media, we can increase the appeal of this area to tourists.